Assessment of tumor necrosis factor- alpha in gingivitis and periodontitis patients - Shrestha, Sajeev; Neupane, Manisha; Sharma, Shivalal; Lamsal, Madhab (International Journal of Dental Research, 2017)
Background: Tumor necrosis factor-α, one of the cytokines, is released in various chronic inflammatory diseases including periodontitis.Aims: To estimate the level of Tumor necrosis factor- alpha (TNF-α) in gingivitis and periodontitis patientsSettings and Design: A cross-sectional study was conducted. A total of 75 patients were recruited by purposive sampling technique among the patients visiting the Department of Periodontology and Oral Implantology during the period one year from August 2014 to July 2015.Material and methods: The recruited samples were divided into gingivitis and periodontitis groups based on clinical attachment level (CAL). A periodontitis subject was defined as having at least 4 sites with pocket depth (PD) >3mm and at least 4 sites with CAL>3 mm, while gingivitis group included the subjects having no CAL measurements greater than 3 mm with signs of inflammation. The TNF-α level was measured using the RayBio Human TNF-alpha ELISA (Enzyme-linked Immunosorbent Assay) kit.Results: The Median TNF-α interquartile range (IQR) (minimum-maximum) in gingivitis and periodontitis was 58.37 (32.63 – 198.77) and 111.89 (39.27 – 215.0) pg/ml, respectively.Conclusion: The level of TNF-α was found to be higher in periodontitis group compared to gingivitis group, although the result was not statistically significant.